Study of Structural, Optical and Electrical Properties of Cadmium Telluride Thin Films - Ajeel, Hayder Mohammad (University of Thi-Qar Journal of Science, 2014)
Prepared of the CdTe thin films by thermal evaporation technique in the vacuum of about 3 × 10−3 torr. in two concentrations(x= 0.2 and x= 0.3) on glass and silicon substrates. In this study we present the effect of increased concentrations of 0.2 and 0.3 on the structural, optical and electrical properties of The CdTe thin films. The structural properties were study by X-ray diffraction (XRD) and XRF results showed that the films were polycrystalline, optical microscope examination and Atomic Force microscopy (AFM) average grain size (24.66 – 12.11 ) nm for (x= 0.2 and x= 0.3) respectively . The optical properties were characterized by UV–VIS spectroscopy and the electrical properties was study.